2012
DOI: 10.2174/092986712802002581
|View full text |Cite
|
Sign up to set email alerts
|

Base Excision Repair: Contribution to Tumorigenesis and Target in Anticancer Treatment Paradigms

Abstract: Cancer treatments often lose their effectiveness due to the development of multiple drug resistance. Thus, identification of key proteins involved in the tumorigenic process and the survival mechanism(s), coupled with the design of novel therapeutic compounds (such as small molecule inhibitors), are essential steps towards the establishment of improved anticancer treatment strategies. DNA repair pathways and their proteins have been exposed as potential targets for combinatorial anticancer therapies that invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 187 publications
(205 reference statements)
1
43
0
Order By: Relevance
“…BER proteins have been broadly explored as targets for cancer therapy (67); in particular, current approaches to cancer treatment report more effective results when specific DNA repair inhibitors are used in combination with DNA damaging drugs. The foremost rationale of the combined therapy is that impairment of BER enzymes is likely to sensitize cancer cells to chemotherapeutic agents.…”
Section: Relevance Of the Unstructured Domain Of Ber Proteins For Desmentioning
confidence: 99%
“…BER proteins have been broadly explored as targets for cancer therapy (67); in particular, current approaches to cancer treatment report more effective results when specific DNA repair inhibitors are used in combination with DNA damaging drugs. The foremost rationale of the combined therapy is that impairment of BER enzymes is likely to sensitize cancer cells to chemotherapeutic agents.…”
Section: Relevance Of the Unstructured Domain Of Ber Proteins For Desmentioning
confidence: 99%
“…Mounting evidence points to the predictive and prognostic value of APE1 expression and subcellular localization in human cancers [24], [25]. For instance, strict APE1 nuclear localization typically associates with a good prognosis, whereas combined cytoplasmic and nuclear localization correlates with poor survival.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has revealed the involvement of polβ in chemoresistance in tumor cells. For example, upregulated polβ expression is associated with resistance to cisplatin in tumor cells (Li et al, 2007;Illuzzi and Wilson, 2012). Previous research by our group further disclosed that GST-π and polβ genes are likely to play an important role in function in MDR in EC9706/ cDDP cells.…”
Section: Discussionmentioning
confidence: 84%